The stranger at hand : antisemitic prejudices in post-Communist Hungary - Kovács, András (Jewish identities in a changing world, 2011)
In 2010 an extremist party with openly racist views, using barely concealed antisemitic language, received 17% of the votes in the parliamentary elections in Hungary. How can this awkward development in a newly established European democracy be explained? In this book the author examines antisemitism in post-communist Hungary in light of the empirical sociological studies of the past 20 years. The principal aim is to reconstruct the range, intensity and content of anti-Jewish prejudices as well as the factors affecting their change over time. The author also reveals the social background again.